Revealing the synergistic effect of capillary force and electrostatic attraction for D-SERS sensitivity. Issue 24 (4th March 2022) - Wang, Weili; Pu, Shuhuan; Hu, Weiye; Gu, Jialei; Ren, Bin; Tian, Zhongqun; Liu, Guokun
Abstract : A method for improving D-SERS sensitivity based on the synergistic effect of capillary force and electrostatic attraction has been developed. Abstract : To overcome the relative weak stability and reproducibility of solid substrates and the long no-signal duration before the short signal-on period of dynamic SERS (D-SERS) strategies, we introduced an electrostatic attraction between the molecule and the D-SERS substrate. The synergistic effect between capillary force and electrostatic attraction during D-SERS measurements improves the SERS sensitivity by 2–3 orders of magnitude compared to that for a solid SERS substrate prepared via liquid–liquid interface self-assembly.